Kemenjadian murid Sekolah Menengah Islam Hidayah, Johor Bahru - Zulkapli, Zuraida (2013)
This study aims to identify the conceptual of student excel in the eyes of citizens Hidayah Islamic School (SMIH), Johor Bahru. This study also view programs on student excel. Also studied was the role of the school community towards student excel. Researchers are also studying improvements can be taken to improve the student excel in SMIH, Johor Bahru. This case study was conducted using qualitative research methods. The findings obtained through interviews. Ten respondents involved in this study consisting of SMIH Principal, Senior Assistances, Hostel Supervisor, Counselors, Parents, Alumni, Tarbiah Teacher, Academic Teachers, Tahfiz Teacher and Support Staffs. The study found that according to the SMIH citizens, student excel conception are to create leaders, to produce Rabbani human, JERI’s balanced human and practiced knowledge human. Identified programs that contribute to student excel are academic, co-curricular and tarbiah. The roles of SMIH citizens in student excel are as implementing and supporting agent. The findings also suggest SMIH citizens should improves in terms of shared vision, cohesion and self quality to sustain student excel in the school.